Targeted complement inhibition using bispecific antibodies that bind local antigens and endogenous complement regulators - Wang, Haiyu; van de Bovenkamp, Fleur S.; Dijkstra, Douwe J.; Abendstein, Leoni; Borggreven, Nicole V.; Pool, Jos; Zuijderduijn, Rob; Gstöttner, Christoph; Gelderman, Kyra A.; Damelang, Timon; Vidarsson, Gestur; Blom, Anna M.; et al. (Frontiers in Immunology, 2024)
Abstract Complement activation protects against infection but also contributes to pathological mechanisms in a range of clinical conditions such as autoimmune diseases and transplant rejection. Complement-inhibitory drugs, either approved or in development, usually act systemically, thereby increasing the risk for infections. We therefore envisioned a novel class of bispecific antibodies (bsAbs) which are capable of site-directed complement inhibition by bringing endogenous complement regulators in the vicinity of defined cell surface antigens. Here, we analyzed a comprehensive set of obligate bsAbs designed to crosslink a specific target with either complement regulator factor H (FH) or C4b-binding protein (C4BP). The bsAbs were assessed for their capacity to inhibit complement activation and cell lysis in an antigen-targeted manner. We observed that the bsAbs inhibited classical, lectin, and alternative pathway complement activation in which sufficient endogenous serum FH and C4BP could be recruited to achieve local inhibition. Importantly, the bsAbs effectively protected antigen-positive liposomes, erythrocytes, and human leukocytes from complement-mediated lysis. In conclusion, localized complement inhibition by bsAbs capable of recruiting endogenous human complement regulators (such as FH or C4BP) to cell surfaces potentially provides a novel therapeutic approach for the targeted treatment of complement-mediated diseases.